Hollow Structure Improved Anti‐Cancer Immunity of Mesoporous Silica Nanospheres In Vivo. Issue 26 (18th May 2016) - Wang, Xiupeng; Li, Xia; Ito, Atsuo; Yoshiyuki, Kazuko; Sogo, Yu; Watanabe, Yohei; Yamazaki, Atsushi; Ohno, Tadao; Tsuji, Noriko M.
Abstract : Hollow and non‐hollow mesoporous silica nanospheres are synthesized and used for cancer vaccine adjuvants. The hollow structure of mesoporous silica nanospheres significantly promote cellular uptake of a model cancer antigen by macrophage‐like cells in vitro, improve anti‐cancer immunity, CD4 + and CD8 + T cell populations in splenocytes of mice in vivo.